Capital Structure Across The Firm Life Cycle: A Moderating Role of Life Cycle in Indonesian Real Estate Sector - Yanuar Dananjaya; Hananiel M Gunawan; Tania M Potu (Universitas Pelita Harapan, 2025)
This study investigates how firm life cycle stages moderate the relationship between capital structure determinants and leverage in the Indonesian real estate sector. Using panel data from listed real estate companies (2009–2024), firms are classified into young and mature groups based on retained earnings to total assets. Our analysis reveals that the firm life cycle is a significant moderator, with findings predominantly supporting the Pecking Order Theory. For young firms, leverage is strongly and negatively driven by liquidity, underscoring their reliance on internal funds. For mature firms, leverage is negatively influenced by profitability and liquidity. Asset tangibility also shows a significant but unexpectedly negative relationship for mature firms, while the tax shield is insignificant for both groups. These findings demonstrate that a firm’s developmental stage is crucial for understanding its capital structure choices, which are shaped by both life cycle-driven financing constraints and sector-specific characteristics